ENERGY SAVING BEHAVIOR THROUGH PEDAGOGICAL STRATEGIES IN ARABIC LANGUAGE LEARNING AT ISLAMIC BOARDING SCHOOL - Asep Sunarko; Hermawan Hermawan (Journal of Economic, Business and Engineering (JEBE), 2026)
This study was motivated by the importance of developing energy-saving behavior in Islamic boarding schools, where students live communally and use electricity, water, and shared facilities in their daily activities. This study aims to analyze the effect of pedagogical strategies in Arabic language learning on students’ energy-saving behavior. A mixed-methods approach was employed using a sequential explanatory design and a quasi-experimental nonequivalent control group design. The participants were 40 students at Nadhrotul Ulum Islamic Boarding School, divided into experimental and control groups. Data were collected through pretest-posttest questionnaires, observations, interviews, and documentation. The results showed that the experimental group’s score increased from 61.40 to 82.15, with a gain score of 20.75, while the control group’s score increased from 60.85 to 67.30, with a gain score of 6.45. The independent sample t-test indicated a significant difference between the two groups, with t = 8.947 and p = 0.000. These findings imply that Arabic language learning can serve as a medium for value education and the formation of sustainable habits in Islamic boarding schools.